Changes in renal gene expression associated with induced ochratoxicosis in chickens: activation and deactivation of transcripts after varying durations of exposure - Zeferino, Cynthia P.; Wells, Kevin D.; Moura, Ana Silvia A M T; Rottinghaus, George E.; Ledoux, David R. (Elsevier, 2017)
Exposure to ochratoxin A (OTA) can lead to changes in global gene expression. This study investigated the individual expression of genes turned on and off in renal cells of chicks after different durations of exposure to dietary OTA. One hundred and eighty day-old male broiler chicks (Ross 308) were randomly assigned to a 3 × 3 factorial arrangement of treatments (3 levels of OTA: 0, 1 and 2 mg OTA/kg diet and 3 time periods: 7, 14 and 21 d). Birds were allocated to 36 pens (4 replicate pens of 5 birds each per treatment). For RNA-Sequencing analysis (RNA-Seq), kidney samples were collected weekly from 3 controls and 3 chicks fed 1 mg OTA/kg. Birds fed 2 mg OTA/kg diet were not chosen for analysis because their reduced feed intake could affect gene expression. The libraries were constructed by Illumina's TruSeq RNA protocol. NextGENe software was used for alignment and transcript quantification. Reads per kilobase of target per million tiled reads (RPKM) were used in the Binary test analysis (P < 0.05). The highest RPKM values were used as criterion for the selection of the genes described. A total of 27,638,976 50-bp RNA-Seq reads were produced over the 3 time periods. Transcripts (40,782) were assembled de novo and annotated by homology to either G. gallus or H. sapiens. The genes activated at 7 d were IL9 and TULP1, at 14 d was GHSR and at 21 d were GRK6 and GAPDH. Unlike all other genes, LOC396365 was activated during all time periods. In contrast, the genes deactivated at 7 d were SPAG4 and LOC100857131, at 14 d were LOC771469, NKX2-1, NKX2-8, FOXO1, MyHC and CLDN18 and at 21 d was XPC. The B-G gene was turned off at 7 and 21 d. All of these genes were involved in kidney toxicity. Therefore, the turning on and off responses of these genes may contribute to carcinogenic and tumorigenic effects of OTA in birds.
Keywords: broiler; mRNA abundance; nephrocarcinogenicity; ochratoxin A; tumor